(untitled) (Global Journal of Computer Science and Technology, 2013)
From his very first novels, CamiloCasteloBranco sought to establish secure codes which, though appearing to subvert implicit rules, were in fact meant to safeguard the legitimacy of his narrative discourse while at the same time giving the impression of engaging readers in light conversation. Thus, the opposition at play between what is true and what appears to be true, as well as between the forced linearity of reading and discursive transgression take on a relevant role in the work of the author from Seide. This tension promotes the construction of novels that constantly seem to question the validity of the diegetic level when compared to the principles revealed in para texts or within the plot. Camilian discourse is thus ironically structured around a continuous ambiguity between saying and doing, while its ingredients unequivocally direct the reader towards the interests of the narrative. AnED;bal Pinto de Castro (1976: 47) had already stressed that this process of manipulation and the consequent excess of justification are indeed common in CamiloCasteloBranco2019;s narrative and they create an ironic overtone which is hard to ignore. When Camilo makes explicit reference to narrative construction processes, he is implicitly alluding to cultural codes that readers are supposed to know and which they will easily identify. Readers are thus in a position to better understand the 2018;game2019; they are being invited to play and which works in two ways: while seemingly legitimizing narrative freedom, it actually reveals observance of the canon.